Speech Perception with Music Maskers by Cochlear Implant Users and Normal Hearing Listeners - Eskridge, Elizabeth N. (J Speech Lang Hear Res, 2012)
OBJECTIVES: The goal of this study was to investigate how the spectral and temporal properties in background music may interfere with cochlear implant (CI) and normal hearing listeners' speech understanding. DESIGN: Sentence recognition thresholds (SRTs) were adaptively measured in 11 CI and 9 NH subjects. CI subjects were tested while using their clinical processors; NH subjects were tested while listening to unprocessed audio. Speech was presented with different music maskers (excerpts from musical pieces), and with steady, speech-shaped noise. To estimate the contributions of energetic and informational masking, SRTs were also measured in “music-shaped noise” and in music-shaped noise modulated by the music temporal envelopes. RESULTS: NH performance was much better than CI performance. For both subject groups, SRTs were much lower with the music-related maskers than with speech-shaped noise. SRTs were strongly predicted by the amount of energetic masking in the music maskers. Unlike CI users, NH listeners obtained release from masking with envelope and fine structure cues in the modulated noise and music maskers. CONCLUSIONS: While speech understanding was greatly limited by energetic masking in both subject groups, CI performance worsened as more spectro-temporal complexity was added to the maskers, most likely due to poor spectral resolution.